Selected Topics in Management and Modeling of Complex Systems: Editorial Introduction to Issue 15 of CSIMQ - Peter Forbrig (Complex Systems Informatics and Modeling Quarterly)
The 15th issue of CSIMQ presents articles discussing management and modeling aspects of informatics research. The provided models and their application help to understand the domains under discussion. The models range from socio-technical models over business process models to models of usable graphical interfaces. Readers might find a lot of interesting aspects in this broad spectrum of management and modeling research. The published articles support management and modeling of complex systems in different ways on different levels of abstraction. The research results reflected in the articles can help to fill knowledge gaps and facilitate decision making in project management, business process management, very complex domain analysis, and data-intensive cyber-physical systems engineering.